What kind of education does China need? The impact of educational attainment on local growth and disparities - Ulrich Reuter (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper analyses the impact of different levels of educational attainment on local growth and economic disparities in China. By applying decomposition analysis and quantile regression techniques to a set of sub-provincial level regional data, special emphasis is put on identifying and incorporating heterogeneities in the educationgrowth relationship across regions and income levels. Previous analyses revealed significant differences in income disparities within provinces across China. So far, no explanation for the cross-provincial pattern of intra-provincial inequality has been offered in the literature. This paper proposes that differences in human capital (proxied by educational variables) affect local growth performance. Can disparities on various levels of education, at least partly, account for the pattern of inter-provincial variation in intra-provincial disparities? – China ; education ; disparities ; decomposition ; quantile regression
Keywords: O15; J24; I21; 330; Bildungsniveau; Regionales Wachstum; Regionale Disparität; China